PENGARUH INDEKS PEMBANGUNAN MANUSIA DAN PRODUK DOMESTIK BRUTO TERHADAP TINGKAT KEMISKINAN DI ASEAN-4 (Studi Pada 4 Negara ASEAN) - Ahmad Syaifullah; Nazaruddin Malik (Jurnal Ilmu Ekonomi JIE, 2017)
Title of this research is  "The Influence of Human Development Index (HDI) and Gross Domestic Product (GDP) on Poverty Rate in ASEAN-4 (Study on 4 ASEAN Countries)". This study aims to determine the effect of Human Development Index (HDI) and Gross Domestic Product (GDP) on the level of poverty in ASEAN-4. Method of data analysis tool used in this research is multiple regression analysis. The results of this study indicate that the Human Development Index (HDI) has a negative and insignificant effect on poverty level in ASEAN-4 with a probabilty value of 0.1149. Then, the Gross Domestic Product (GDP) has a negative and significant effect on the poverty level in ASEAN-4 with a probability value of 0.0000. Keywords: Gross Domestic Product (GDP), Human Development Index (HDI), Poverty